Genomic Characterization of the Japanese Indigenous Wine Grape Vitis sp. cv. Koshu - Tanaka, Keisuke; Hamaguchi, Yu; Suzuki, Shunji; Enoki, Shinichi (Frontiers in Plant Science, 2020)
Vitis sp. cv. Koshu is indigenous to Japan and used as table and processing grapes. It is also one of the most important grape cultivars in white wine making. To understand its genomic information, we compared small and structural variations with table grape cultivar “Thompson seedless” and European wine grape cultivar “Tannat” by a resequencing approach. Koshu genome had high heterozygosity, and this characteristic was particularly prominent in chromosome 7. Koshu genome exhibited different genomic variations and structures from comparative two grape cultivars. Plant disease resistance shown by cell death associated with hypersensitive response, and environmental stress response, such as water deprivation, oxidative stress, and cell wall organization, were suggested by enrichment analysis of small and structural variations. Mutation accumulation levels in Koshu indicated that phenylpropanoid, flavonoid, glutathione, and α-linolenic acid pathways were related to polyphenol and flavor components. The genomic information of Koshu would be important not only for improving the quality of Koshu wine and but also for using Koshu as a genetic resource.